Biologia floral e polinização diurna e noturna de Ipomoea carnea subsp. fistulosa (Mart. ex Choisy) D.F. Austin (Convolvulaceae) em uma área antropizada no semi-árido da Bahia, Brasil - Paz, Joicelene Regina Lima da (2011)
Flowers of Ipomoea are characterized mainly by be ephemeral and showy, attracting a lot floral visitors belong to different taxonomic groups and are generally synchronized with the times of opening and closing of flowers. In this study we proposing to relate aspects of flowering, morphology and floral biology of Ipomoea carnea subsp. fistulosa with the dynamics of the pollinators and the meteorological and environmental factors, with emphasis on temporal and behavioral aspects in different months of the year, in an anthropic area of the Bahia semiarid. Monthly observations were made for three days (72 h), between October/09 and August/10 on the Campus of UEFS (BA), to investigate the morphology and floral biology, reproductive system, aspects of flowering and collects of floral visitors. The flowering of this plant occurred during all months, when the individuals produced flowers that opened during the three periods of the day, morning, afternoon and evening, with a longevity of 11, 19 and 16 hours respectively. This species is self-incompatible and the flowers were visited predominantly by bees and moths presenting morphological traits common to the syndromes melittophily and phalaenophily. The conspicuous pink color of the flowers attracts the bees and the strong sweet scent during the evening attracts the moths. The bees Apis mellifera, Melitoma aff. segmentaria, Pseudoaughlcora Pandora were considered the potential diurnal pollinators and the hawkmoths Agrius cingulata the potential night pollinator. The exhibition of the flowers for 24 hours, attracting visitors day and night, increases the chances of pollination, especially in ruderal and weedy species as I. carnea subsp. fistulosa.